Implementation of Child Friendly Village Regulations in Sumbawa Regency - Irawansyah, Irawansyah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This reseach aims to find out how the child-friendly village program is evaluated and what are the inhibiting factors that influence te implementation of the child-friendly village program that has been estabilished in Poto village. In this research itself qualitative methods are used, where data collection uses three strages, namely, observation, interviews, and documentation as reinforcement.The results obtained in this research are knowing the process of policy formulation stages which include problem formulation, policy agenda, slection of policy alternatives, and policy determination. And also fulfilling the indicator components of the public policy sytem.